Pengaruh Penyuluhan Tentang Pola Makan pada Penderita Diabetes Dengan dan Tanpa Komplikasi di Kecamatan Getasan - Elian Gina Hapsari; Junet Franzisca da Costa; Franzesca Dwi Wahyu (Universitas Muhammadiyah Kalimantan Timur, 2017)
Diabetes Meliitus (DM) is an incurable disease or life-alive disease. Management of diabetes mellitus is not only dependent on health workers, patients and families also have an important role in controlling blood sugar levels.Diabetes mellitus often appear along with the incidence of uric acid and hypertension due to imbalance of normal components. The research was conducted in Getasan Subdistrict and aimed to see if there is any relationship between diabetes mellitus with the occurrence of uric acid and hypertension and to see the effect of counseling given to dietary change of DM patient. The results showed that diabetes had a significant relationship with uric acid containing p = 0.040 (<0.05) and the counseling did not affect the diet of the research samples in which the statistical test result was 0.478 (> 0.005).